Pleomorphic Adenoma Presenting as an Atypical Nasal Mass in a 26-Year-Old Female - Racheal Hapunda; Chibamba Mumba; Owen Ngalamika (Case Reports in Surgery)
Pleomorphic adenoma (PA) is a salivary gland tumor that may rarely occur in the nasal cavity. It can be a clinical diagnostic dilemma in many instances due to many possible differential diagnoses. We report the case of a 26-year-old female who presented with a 3-year history of a right nasal growth associated with ipsilateral nasal blockage, nasal pain, and rhinorrhea. Radiological image showed a mild enhancing lesion in the right nasal cavity. The patient underwent a lateral rhinotomy with wide excision of the mass. Histopathological exam was consistent with PA. Nasal PA is a rare entity and should be suspected as a diagnosis for intranasal tumors.